Antibiotic‐prescribing patterns of South African dental practitioners following tooth extractions. Issue 4 (24th October 2016) - Lalloo, Ratilal; Solanki, Geetesh; Ramphoma, Khabiso; Myburgh, Neil G.
Abstract: Aim: In the present study, we assessed the patterns and types of antibiotics prescribed following tooth extractions, and the alignment of these practices with the evidence available. Methods: The study used health insurance claim data from South African dental practitioners for 2013, analyzing the antibiotic prescribing patterns around tooth extractions, separately for four event types: exposed (simple) tooth extractions in: (a) healthy patients and (b) patients with chronic conditions; and impacted tooth extractions in (c) healthy patients and (d) patients with a chronic condition. Results: More than 50 000 extraction events were analyzed. The findings show no consistency in prescribing patterns. The same percentage (10%) of the healthy and the chronically ill patients undergoing an exposed (simple) tooth extraction were prescribed antibiotics, while approximately 50% of both healthy and chronically ill patient groups undergoing an impacted tooth extraction received a prescription. Almost 81% of prescriptions were for narrow spectrum antibiotics, with few differences across the four event types. Conclusions: The antibiotic prescription patterns of dental practitioners reported in the present study do not appear to follow a coherent set of guidelines or meaningful indications for antibiotic use. The study highlights the need for explicit and more prudent guidelines for the use of antibiotics following tooth extractions, to reduce the risk of antibiotic resistance.